2022
DOI: 10.1093/plphys/kiac533
|View full text |Cite
|
Sign up to set email alerts
|

FER and LecRK show haplotype-dependent cold-responsiveness and mediate freezing tolerance in Lotus japonicus

Abstract: Many plant species have succeeded in colonizing a wide range of diverse climates through local adaptation, but the underlying molecular genetics remain obscure. We previously found that winter survival was a direct target of selection during colonization of Japan by the perennial legume Lotus japonicus and identified associated candidate genes. Here, we show that two of these, FERONIA-receptor like kinase (LjFER) and a S-receptor-like kinase gene (LjLecRK) are required for non-acclimated freezing tolerance and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…It is characterized by two malectin-like domains, a transmembrane domain and an intracellular Ser/Thr kinase domain [ 114 ]. CrRLK1L receptor kinase plays an important role in regulating plant growth and development and coping with various stresses [ 115 , 116 , 117 , 118 , 119 , 120 , 121 , 122 , 123 , 124 , 125 ]. At present, 17 and 20 hypothetical CrRLK1L members have been retrieved from Arabidopsis and rice genomes [ 126 ], and some of their functions have been identified ( Figure 4 ).…”
Section: Rlk-mediated Molecular Crosstalk Between Plant Growth and St...mentioning
confidence: 99%
“…It is characterized by two malectin-like domains, a transmembrane domain and an intracellular Ser/Thr kinase domain [ 114 ]. CrRLK1L receptor kinase plays an important role in regulating plant growth and development and coping with various stresses [ 115 , 116 , 117 , 118 , 119 , 120 , 121 , 122 , 123 , 124 , 125 ]. At present, 17 and 20 hypothetical CrRLK1L members have been retrieved from Arabidopsis and rice genomes [ 126 ], and some of their functions have been identified ( Figure 4 ).…”
Section: Rlk-mediated Molecular Crosstalk Between Plant Growth and St...mentioning
confidence: 99%
“…In the Arabidopsis mutant feronia ( fer ), the pollen tube fails to arrest and thus continues to grow inside the female gametophyte without rupture for the release of sperms [ 17 , 18 ]. Besides the role in reproduction, accumulating evidence suggests that FER plays critical roles in a diversity of biological processes, such as root growth [ 135 , 136 , 137 ], immune responses [ 21 , 138 , 139 , 140 , 141 , 142 ], environmental adaptations [ 143 , 144 , 145 , 146 ], etc.…”
Section: Cwi Signal Candidates In Fruit Ripeningmentioning
confidence: 99%
“…GWAS and epigenome wide association studies (EWAS) for the 60 Populus tomentosa hub genes identified that LecRK-VIII.2 is associated with chlorophyll content among different methylotypes (Zhou et al, 2023). Using in-field overwinter survival as a trait, another GWAS and population differentiation analysis in Lotus japonicas revealed that LjLecRK is required for non-acclimated freezing tolerance and haplotype dependent cold responses (Shah et al, 2020;Mustamin et al, 2023). As there is tremendous natural variation in LecRKs, more LecRKs may be identified by GWAS analysis combined with different biotic or abiotic treatments in the future.…”
Section: Natural Variation Of Lecrksmentioning
confidence: 99%
“…Thus, transferring AtLORE to crops, such as rice, might enable the engineering of resistance traits to bacteria, such as Xanthomonas species, or constructing transgenic plants with chimeric LecRKs will achieve a potentially important step toward generating pathogen resistant crops (He et al, 2019). Meanwhile, LjLecRK of Lotus japonicas, plays important roles in freezing tolerance (Mustamin et al, 2023). SIT1 mediates ethylene production and salt-induced ethylene signaling (Li et al, 2014).…”
Section: Applications In Crop Improvementmentioning
confidence: 99%